Mechanical Ventilation Induces Interleukin 4 Secretion in Lungs and Reduces the Phagocytic Capacity of Lung Macrophages. (13th November 2017) - Bielen, Kenny; 's Jongers, Bart; Boddaert, Jan; Lammens, Christine; Jorens, Philippe G; Malhotra-Kumar, Surbhi; Goossens, Herman; Kumar-Singh, Samir
Abstract : This study demonstrates that mechanical ventilation causes interleukin 4 (IL-4)–mediated immunosuppression and reduced bacterial phagocytosis that impacts pneumonia development in rodents. Blocking of IL-4 signaling restores the phenotype, suggesting that induction of IL-4 due to mechanical ventilation predisposes to pneumonia development. Abstract: Patients receiving mechanical ventilation are at risk of developing ventilator-associated pneumonia. Here, we show that clinically utilized ventilation protocols in rats with 5 mL/kg or 8 mL/kg tidal volumes cause increased interleukin 4 (IL-4) expression, lowered ratio of TH 1:TH 2 transcriptional factors ( Tbet : Gata3 ), and increased arginase 1–positive (Arg1 + ) macrophages and eosinophils in lungs. Macrophages from ventilated lungs had reduced ex vivo capacity toward phagocytosing bacteria. Ventilated animals, when further challenged with bacterial pneumonia, continued to show persistence of Arg1 + M2 macrophages as well as an increased bacterial burden compared with spontaneously breathing animals receiving the same bacterial dose. Increased IL-4 expression also occurred in a mouse ventilation model, and abrogation of IL-4 signaling restored lung bacterial burden in an IL-4Rα −/− ventilator-associated pneumonia model. Our data suggest that mechanical ventilation induces an immunosuppressive state in lungs, providing new insight in the development of ventilator-associated pneumonia.